preventing of osteoporosis: Applying the Health Belief Model - Mahdavi, shila; Karimzadeh shirazi, Kambiz; Malekzadeh, JanMohammad; Fararooei, Mohammad (Advances in Nursing & Midwifery, 2015)
Background and aim: osteoporosis as a disease, is characterized by low bone mass and loss of bone microstructure known. According to the importance of identifying the preventive behaviors in premenopausal women by nurses and other health personnel, This study aimed to determine the predicting factors of nutritional behaviors for preventing of osteoporosis according to the Health Belief Model was performed. Materials and Methods: This cross-sectional study was conducted on 147 women aged 35-49 were referred to Health Centers in Bandar Abbas, Iran. A systematic cluster sampling method was applied. Data collection tool was included demographic information, knowledge, health belief model constructs and calcium and vitamin D rich foods frequency questionnaires. The data were analyzed using descriptive statistical, Pearson Correlation and Linear Regression. Findings: The result showed that self-efficacy, perceived benefits, perceived barriers had a significant relationship with nutritional behaviors . Structure barriers predict calcium intake. Also, Structural barriers and perceived benefits were identified as strong predictors for vitamin D. Conclusion: According to the results, The health belief model could become suitable framework for interventional programs, However, taking into account social -cultural factors related to the preventive behaviors could have effective role for improving preventive nutritional measures. Keywords: nutritional behavior, osteoporosis, prevention, health belief model